Mergers and acquisitions in Greece: stock price reaction of acquiring and target firms - Πρωτόπαπας, Παναγιώτης Π.; Τραυλός, Νικόλαος Γ.; Τσαγκαράκης, Νικόλαος Β. (SPOUDAI Journal of Economics and Business, 2003)
This study examines the stock price reaction to mergers and acquisitions on the announcement day by firms listed on the Athens Stock Exchange. Using an event study methodology we investigate firms that participated in mergers and acquisitions as buyers or targets during the period 1988-1997. Our findings show that mergers and acquisitions in Greece are associated with statistically significant abnormal returns for both the acquiring and target firms. Thus, mergers and acquisitions in Greece create wealth shared by both parties involved in a corporate restructuring. JEL Classification: G34